Rings with finite decomposition of identity - Dokuchaev, M.A.; Gubareni, N.M.; Kirichenko, V.V. (Український математичний журнал, 2011)
A criterion for semiprime rings with finite decomposition of identity to be prime is given. We also give a short survey on some finiteness conditions related to the decomposition of identity. We consider the notion of a net of a ring and show that the lattice of all two-sided ideals of a right semidistributive semiperfect ring is distributive. An application of decompositions of identity to groups of units is given. Наведено критерiй первинностi напiвпервинних кiлець iз скiнченним розкладом одиницi, а також короткий огляд деяких умов скiнченностi вiдносно розкладу одиницi. Розглянуто поняття сiтки кiльця i показано, що решiтка всiх двобiчних iдеалiв правого напiвдистрибутивного напiвдосконалого кiльця є дистрибутивною. Наведено застосування розкладу одиницi до груп одиниць.